Cost Benefit Analysis of Investment Projects, based on Inter-Industry Models - KOGAN, Anton (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
This paper offers solution to some problems of cost benefit analysis. Guides to cost benefit analysis require calculating externalities of an appraised project, but don't discuss universal models and calculation methods. The author suggests that inter-industry models should be used to appraise externalities, with positive externalities being full benefits of the economy and negative externalities being full costs of the economy. Factors of full material costs are used for calculation. Thus, the depth and accuracy of cost benefit analysis (CBA) is increased, with the share of subjectivism in such appraisal being reduced. It is not required to use the conversion factor to change prices of inputs and outputs. The economic efficiency is appraised on the basis of ‘the index of specific value growth speed’ (IS) developed by the author. The author proves that only IS (but not net present value) makes it possible to compare the efficiency of alternative projects with different investment amounts, calculation periods and annual results.
Keywords: cost benefit analysis; economic efficiency appraisal; inter-industry models